Urgensi dan Optimalisasi Pajak Elektronik sebagai Sistem Perpajakan Terintegrasi untuk Meningkatkan Aksesibilitas Wajib Pajak - Triyanto; Ismiyanto; Muhtarom, M. (Fakultas Hukum Universitas Mulawarman, 2024)
Technological advancements necessitate the adaptation of taxation systems to meet the dynamic needs of society. This study examines two primary issues: (i) why integrated taxation through electronic tax systems is essential for enhancing taxpayer accessibility, and (ii) how the optimization of electronic tax systems as an integrated taxation framework can achieve this goal. The integration of information technology in the form of electronic tax systems plays a strategic role as a tax database accessible to both the government and taxpayers, minimizing errors in tax calculation and payment. This study employs a normative juridical method, focusing on the application of principles and norms within the national taxation system. The findings reveal the critical need for integrated taxation through electronic tax systems as a solution to tax collection challenges and for improving the quality of tax databases. The optimization of this system can be realized through the development of technical implementation guidelines, including system strengthening and maintenance, capacity building for human resources, and effective monitoring mechanisms.